Research on pressure compensation and friction characteristics of piston rod seals with different degrees of wear. (February 2020) - Zhao, Xiuxu; He, Xiangyu; Wang, Liting; Chen, Peng
Abstract: In this paper, a pressure compensated sealing method is proposed to solve the problem that the piston rod seal does not have the sealing compensation capability after wear. The pressure compensation simulation and experimental research on piston rod seals with different degrees of wear were carried out. In the experimental study, the monitoring data was collected by fiber Bragg grating sensors, tension sensors, pressure sensors and displacement sensors, and the parameters that reflect the sealing performance and friction characteristics are extracted therefrom. The relationship between the compensation pressure and the parameters under different degrees of wear was analyzed. The results show that the pressure compensation sealing method can improve the sealing performance of the sealing ring. Highlights: A pressure compensation method is proposed to improve the sealing ability after the seal is worn. The method was verified by piston rod seals with different degrees of wear. Nine parameters were extracted from the data collected by the four sensors. The pressure compensation seal has certain sealing compensation ability. The relationship of the sealing performance and friction characteristics is revealed.